Characterization of a p.R76H mutation in Cx50 identified in a Chinese family with congenital nuclear cataract - Kai Jie Wang; Jin Da Wang; Dou Dou Chen; Ming Yang Wang; Bo Yun; Si Quan Zhu (Journal of the Formosan Medical Association, 2020)
Background/purpose: A three-generation Chinese family with autosomal dominant congenital nuclear cataract was recruited. This study aimed to identify the disease-causing gene for nuclear cataract with functional dissections of the identified mutant. Methods: Detailed clinical data and family history were recorded. Candidate gene sequencing was performed to identify the disease-causing mutation. Recombinant connexin50 (Cx50) wild type and mutant constructs were synthesized. Triton X-100 solubility and subcellular localization of the recombinant Cx50 proteins were analyzed in HeLa cells. Apoptosis was assayed as the percentage of fragmented nuclei in transfected cells. Results: All affected individuals in the family displayed clear phenotypes of dense nuclear cataracts. A c.227 G > A variation was found in the coding region of Cx50, which arginine residue at position 76 was substituted by histidine (p.R76H). This mutation was co-segregated with the disease in the family, and was not observed in 110 unrelated Chinese controls. No statistically significant differences were found in the Triton X-100 solubility and apoptosis rate between wild type and mutant Cx50 in HeLa cells. However, Cx50 mutant was unable to form gap junctional plaques between adjacent cells as the wild type proteins did. Conclusion: This study identified a novel cataract phenotype caused by the p.R76H mutation in Cx50, providing evidence of further phenotypic heterogeneity associated with this mutation. Functional analysis showed that the mutation affected the formation of gap junction channels and led to opacity in the lens. Keywords: Gap junction, Mutation, Nuclear cataract